Optimization of Fuel System Maintenance for Smooth Operation of Main Engines on KM Pratama Mas Ship - Permadi, Yudha Sali; Mursidi, Mursidi; Saktiono, Maxima Ari (Universitas Hang Tuah, 2026)
The main engine is the primary component in a ship's propulsion system, responsible for the continuity of its voyages. A critical supporting system for the main engine's performance is the fuel system. This system supplies fuel at the correct pressure and quantity to the combustion chamber, ensuring optimal combustion. Any disruption or irregularity in the fuel system can cause the main engine's performance to decline, potentially leading to serious damage that hinders the ship's operation. This study aims to analyze the factors causing fuel inefficiency in the main engine and to formulate technical recommendations to address these issues. The research uses a descriptive qualitative approach through direct observation, interviews with the ship's crew, and a literature review. The results indicate that the main causes of these issues include:An increase in exhaust gas temperature due to the fuel injector's operating hours exceeding its maintenance schedule, leading to the injector not functioning optimally.The main engine shutting down unexpectedly due to dirt and water in the fuel, which interfered with the fuel purifier's operation, resulting in poor fuel quality.The suggested solutions include installing a separator to achieve better fuel quality and increasing the temperature of the MFO fuel. It is hoped that the findings of this research can serve as a reference for fuel system maintenance to improve the ship's operational reliability and efficiency.